Two New Species of Dicyemids (Phylum Dicyemida) from Octopus conispadiceus (Mollusca: Cephalopoda: Octopoda) in Japanese Waters - Hidetaka Furuya (Species Diversity, 2025)
Two new species of dicyemids are described from an octopus, Octopus conispadiceus (Sasaki, 1917), collected off Shiranuka, Hokkaido, Japan. Dicyemennea tsunekii sp. nov. is a large species that reaches about 1 mm in length. The vermiform stage is characterized by 33–35 peripheral cells, a conical calotte, and an axial cell that extends to the base of the metapolar cells. The infusoriform embryo consists of 39 cells; two nuclei are present in each urn cell and the refringent bodies are solid. Dicyemodeca shirarikaense sp. nov. is a medium-sized species that reaches about 2.5 mm in length. The vermiform stage is characterized by 24 peripheral cells, a cap-shaped calotte, and an axial cell that extends to the base of the propolar cells. The infusoriform embryo consists of 35 cells; two nuclei are present in each urn cell and the refringent bodies are liquid.